2017
DOI: 10.1021/acs.accounts.7b00329
|View full text |Cite
|
Sign up to set email alerts
|

C- and N-Metalated Nitriles: The Relationship between Structure and Selectivity

Abstract: Metalated nitriles are exceptional nucleophiles capable of forging highly hindered stereocenters in cases where enolates are unreactive. The excellent nucleophilicity emanates from the powerful inductive stabilization of adjacent negative charge by the nitrile, which has a miniscule steric demand. Inductive stabilization is the key to understanding the reactivity of metalated nitriles because this permits a continuum of structures that range from N-metalated ketenimines to nitrile anions. Solution and solid-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 85 publications
2
25
0
Order By: Relevance
“…Nitrile anions are a diverse class of synthetic intermediates that provide access to highly functionalized products through nucleophilic addition and substitution reactions . Analogous to enolates, nitrile anions are ambident nucleophiles that can react either as carbanions to provide α‐functionalized cyano products,– or as keteniminates to provide neutral ketenimines . Each product class has further synthetic utility as building blocks for natural products and pharmaceuticals; while α‐cyano groups are easily derivatized, ketenimines further undergo nucleophilic, electrophilic, and/or cyclization reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrile anions are a diverse class of synthetic intermediates that provide access to highly functionalized products through nucleophilic addition and substitution reactions . Analogous to enolates, nitrile anions are ambident nucleophiles that can react either as carbanions to provide α‐functionalized cyano products,– or as keteniminates to provide neutral ketenimines . Each product class has further synthetic utility as building blocks for natural products and pharmaceuticals; while α‐cyano groups are easily derivatized, ketenimines further undergo nucleophilic, electrophilic, and/or cyclization reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, cation coordination in 1-M can either occur at the cyanido nitrogen or at the a-carbon [a] C. Schwarz, + L. T. Scharf, + T. Scherpf atom. These different coordination modes have been shown to influencet he reactivity of variousm etalated nitriles [11,12] and are expected to affect the bonding situation. Comparable to CDPs, the electronic structure in yldiides can be described by different bonding situations.I nt he past, the ylidic form 1A (Figure 2) was used to account for the two lone pairs at the central carbon atom and the high nucleophilicity, which have both been experimentally provenb yt he use in double-functionalization and cascadereactions or in the formation of digold complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent reorientation with attack from the carbon of the cyanide ion on the carbene [5] would generate a lithiated nitrile whose alkylation would afford the corresponding quaternary nitrile. [6] The speculation led to screening several additives known to suppress carbene formation: [7] HMPA, 18-crown-6, LiCl, DMPU, DME, KOtBu and TMEDA. TMEDA proved optimal in suppressing the rearrangement, allowing for sulfanyl-lithium exchange-alkylations for a variety of electrophiles; [1] the exchange-stannylation of 2b to afford isocyanide 2d [8] is representative (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The limited stability of metalated isocyanides suggested that the rearrangement might involve cyanide expulsion with formation of a carbene. Subsequent reorientation with attack from the carbon of the cyanide ion on the carbene would generate a lithiated nitrile whose alkylation would afford the corresponding quaternary nitrile . The speculation led to screening several additives known to suppress carbene formation: HMPA, 18‐crown‐6, LiCl, DMPU, DME, KO t Bu and TMEDA.…”
Section: Resultsmentioning
confidence: 99%